Towards a more robust representation of lithic industries in archaeology: a critical review of traditional approaches and modern techniques - Looten, Julien; Gravina, Brad; Muth, Xavier; Villaeys, Maxime; Bordes, Jean-Guillaume (Peer Community Journal, 2025)

(untitled)
Often comprising vast numbers of artifacts, prehistoric lithic assemblages are presented in publications in the form of drawings, diagrams, photographs, or extracts from 3D acquisitions. These visual representations are designed to highlight the most characteristic typological and technological features of a given assemblage. However, the selection of pieces to illustrate is dictated by constraints of time, budget, or space. Moreover, inaccuracies in drawings or poorly lit photographs can cause confusion and problems of interpretation, while more precise, complex, or time-consuming methods can only be applied to a limited number of objects. After a brief overview of the advantages and limitations of the main types of stone tool representations, namely standard drawing and photography, we detail the acquisition of 3D models through photogrammetry in relation to Reflectance Transformation Imaging (RTI). Although less widely known than 3D imaging, RTI is an inexpensive, easily transferred photographic method that can be performed using non specialist equipment. It allows for the visualization of an object’s interactions with artificial light and enhances the perception of its microtopography. RTI provides a more comprehensive documentation of stone tools, including flake scars, use-wear traces, and post-depositional alterations, and thereby enhances the accuracy and, by extension, the objectivity of stone tool representations and artifact characterization.